Recurrent Intestinal Intussuseption in Adult: A Case Report - Yusuf Yucel; Orhan Gozeneli; Alpaslan Terzi; Ahmet Seker; Abdullah Ozgonul; Ali Uzunkoy; Mahmut Toprak (Namık Kemal Tıp Dergisi, 2016)

(untitled)
Intussusseption is an usually incident that may present in pediatric patients but we encounter rarely in adults. It leads to obstruction of the gastrointestinal tract. In pediatric patients, etiological factors are due to benign incidents usually, but in adults, often depends on tumors. Etiological factors should be investigated after obtaining the reduction of intussusception and intraluminal pathologies should be excluded. It will cause to intussusseption recurrence after years if reduction perform without treating etiological factors.